Formação superior de oficiais da polícia de Moçambique: articulação entre os fundamentos teóricos e as habilidades práticas - Tsucana, Fernando Francisco (2014)
This research is focused on the relationship between theory and practice in the course of higher education of police officers given by the Academy of Police Sciences (ACIPOL) of Mozambique. Starting from the concern that the training offered by ACIPOL has been predominantly theoretical, methodological procedures used in teaching practice do not establish a connection with actual police practices; this study promotes, through supervised traineeship and pre-professionals practices, the relationship between the theoretical and practical skills training. Based on fundamentals of critical and reflective pedagogy , this study has used both quantitative and qualitative research tools to investigate a group of the Republic of Mozambique Police (PRM) officers in active, collecting their opinions and perceptions on issues affecting officer training offered by ACIPOL. As a result, this study raises the proposition that the courses should have a basic core training that is not simply structured around disciplines that finished passing along content, but be able to transform the current organization of scientific areas into learning axles, properly integrated and articulated with theoretical underpinnings and skills required for future professional role of learners. This implies a new conception of the learning activities, the training process, the training spaces and actors